RELATIONSHIP BETWEEN INVESTMENT DECISIONS, ENVIRONMENTAL CONCERNS AND ENVIRONMENTAL PERFORMANCE ON CORPORATE SOCIAL RESPONSIBILITY - Musfialdy, Musfialdy (Universitas Brawijaya, Indonesia, 2019)
Corporate Social Responsibility (CSR) is an approach that integrates social care into a company’s business operations and its interactions with stakeholders. The approach is based on voluntary and partnership principles. CSR awareness is needed as a form of concern for the interests of stakeholders. CSR is not only volunteerism, but also it has become a demand for companies if they want to survive and develop. This study aims to analyze the influence of investment decisions, environmental concerns and environmental performance on CSR. The population were all mining companies listed on the Indonesia Stock Exchange from 2013-2016. A total of nine companies met the selection criteria. Results using linear regression indicate that investment decisions, environmental, performance concerns positively and significantly affect the extent of CSR. Further research can extend the period of observation. The samples in other sectors on the Indonesian Stock Exchange.